Targeting NPM1 in irradiated cells inhibits NPM1 binding to RAD51, RAD51 foci formation and radiosensitizes NSCLC. (1st March 2021) - Traver, Geri; Sekhar, Konjeti R.; Crooks, Peter A.; Keeney, Diane S.; Freeman, Michael L.
Abstract: The ability of chemo-radiation therapy to control locally advanced stage III non-small cell lung cancer (NSCLC) is poor. While addition of consolidation immunotherapy has improved outcomes in subsets of patients there is still an urgent need for new therapeutic targets. Emerging research indicates that nucleophosmin1 (NPM1) is over-expressed in NSCLC, promotes tumor growth and that over-expression correlates with a lower survival probability. NPM1 is critical for APE1 base excision activity and for RAD51-mediated repair of DNA double strand breaks (DSBs). YTR107 is a small molecule radiation sensitizer that has been shown to bind to NPM1, suppressing pentamer formation. Here we show that in irradiated cells YTR107 inhibits SUMOylated NPM1 from associating with RAD51, RAD51 foci formation and repair of DSBs. YTR107 acts synergistically with the PARP1/2 inhibitor ABT 888 to increase replication stress and radiation-induced cell lethality. YTR107 was found to radiosensitize tumor initiating cells. Congruent with this knowledge, adding YTR107 to a fractionated irradiation regimen diminished NSCLC xenograft growth and increased overall survival. These data support the hypothesis that YTR107 represents a therapeutic target for control of NSCLC. Highlights: The small molecule YTR107 inhibits NPM1 from binding to RAD51. YTR107 inhibits RAD51 recruitment to DNA DSBs. YTR107 inhibits repair of DNA DSBs. YTR107 radiosensitizes tumor initiating cells and tumor xenografts.